2020
DOI: 10.4269/ajtmh.20-0122
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Cardiac Magnetic Resonance T1 Mapping Parameters and Ventricular Arrhythmia in Patients with Chagas Disease

Abstract: Chronic Chagas disease can progress to myocardial involvement with intense fibrosis, which may predispose patients to sudden cardiac death through ventricular arrhythmia. The associations of myocardial fibrosis detected by cardiac magnetic resonance (CMR) parameters with non-sustained ventricular tachycardia (NSVT) were evaluated. This cross-sectional study included patients in early stages of Chagas disease (n = 47) and a control group (n = 15). Patients underwent cardiac evaluation, including CMR examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
1
12
0
3
Order By: Relevance
“…The combined analysis of studies reporting delayed enhancement in patients with the indeterminate form shows the occurrence of myocardial scar in 19% of the pooled population (Table 1). 9,10,[32][33][34][35][36][37][38][39] Myocardial fibrosis progressively increases with disease progression, being considered a marker of CCDC severity. 9 The higher the proportion of delayed enhancement in relation to the LV mass, the lower the ejection fraction of this chamber and the worse the estimated functional class.…”
Section: Myocardial Fibrosis and LV Systolic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined analysis of studies reporting delayed enhancement in patients with the indeterminate form shows the occurrence of myocardial scar in 19% of the pooled population (Table 1). 9,10,[32][33][34][35][36][37][38][39] Myocardial fibrosis progressively increases with disease progression, being considered a marker of CCDC severity. 9 The higher the proportion of delayed enhancement in relation to the LV mass, the lower the ejection fraction of this chamber and the worse the estimated functional class.…”
Section: Myocardial Fibrosis and LV Systolic Dysfunctionmentioning
confidence: 99%
“…A crosssectional study of 47 Chagas patients demonstrated that higher interstitial fibrosis by its CMR-derived extracellular volume is associated with non-sustained ventricular tachycardia regardless of ejection fraction and delayed LV myocardial enhancement quantification. 38…”
Section: Review Articlementioning
confidence: 99%
“…The combined analysis of studies reporting delayed enhancement in patients with the indeterminate form shows the occurrence of myocardial scar in 19% of the pooled population (Table 1). 9,10,[32][33][34][35][36][37][38][39] Myocardial fibrosis progressively increases with disease progression, being considered a marker of CCDC severity. 9 The higher the proportion of delayed enhancement in relation to the LV mass, the lower the ejection fraction of this chamber and the worse the estimated functional class.…”
Section: Myocardial Fibrosis and LV Systolic Dysfunctionmentioning
confidence: 99%
“…Nevertheless, prognosis should not be entirely based on MF since there are other findings that CMR also identifies and are equally important to detect as early as possible on the disease’s natural history, including myocardial edema, aneurysm formation, intracavitary thrombus, and focal and diffuse fibrosis in the noted territories [ 84 , 85 , 86 , 87 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%